Development of Arabic Language Exam Questions Based on CEFR and SKKNI Through The LMS Website - Marsekal Rahman Hakiem; Muhammad Irfan Faturrahman; Ahmad Luqman Hakim; Ach. Afrian Auliansyah; Lutfi Bangun Lestari (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This study aims to develop Arabic language test questions based on the Common European Framework of Reference for Languages (CEFR) and the Indonesian National Work Competency Standards (SKKNI), and to present them online via the Learning Management System (LMS). This study is part of an effort to develop an Arabic language evaluation instrument that is more communicative, accountable, and aligned with global and national needs. The instrument development process was carried out using the ADDIE model across the analysis, design, development, implementation, and evaluation stages. The test was then administered to 212 students. The evaluation revealed a decline in CEFR level achievement from pre-test to post-test, indicating a more accurate measurement of Arabic language proficiency. Interviews with 57 participants confirmed that the test items were perceived as more challenging and that they reflected real Arabic language use. These findings demonstrate the success of integrating the CEFR and SKKNI to produce a more targeted and high-quality Arabic language evaluation instrument.